Structural Characteristics, Binding Partners and Related Diseases of the Calponin Homology (CH) Domain - Yin, Lei-Miao; Schnoor, Michael; Jun, Chang-Duk (Frontiers in Cell and Developmental Biology, 2020)
The calponin homology (CH) domain is one of the most common modules in various actin-binding proteins and is characterized by an α-helical fold. The CH domain plays important regulatory roles in both cytoskeletal dynamics and signaling. The CH domain is required for stability and organization of the actin cytoskeleton, calcium mobilization and activation of downstream pathways. The CH domain has recently garnered increased attention due to its importance in the onset of different diseases, such as cancers and asthma. However, many roles of the CH domain in various protein functions and corresponding diseases are still unclear. Here, we review current knowledge about the structural features, interactome and related diseases of the CH domain.